Composition for forming a hard coat layer and hard coat film

JP7939929B2Active Publication Date: 2026-10-22TOYOCOLOR CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023217525
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2026-10-22
Estimated Expiration
2043-12-25

AI Technical Summary

Benefits of technology

【0014】 本発明のハードコート層形成用組成物を用いることによって、透明性、アンチブロッキング性、防汚性、傷付き防止性を兼ね備えたハードコート層を形成することが可能な組成物を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007939929000001
    Figure 0007939929000001
  • Figure 0007939929000002
    Figure 0007939929000002
  • Figure 0007939929000003
    Figure 0007939929000003
Patent Text Reader

Abstract

To provide a composition for forming hard coat layers, the composition having superior coatability and enabling formation of hard coat layers having transparency, anti-blocking performance, antifouling performance, scratch resistance, and curability.SOLUTION: A composition for forming hard coat layers contains: a compound (A) having one or two ethylenically unsaturated groups, a viscosity of 1-30 mPa s at 25°C, and a boiling point of 200°C or higher at an atmospheric pressure of 1 atm; a compound (B) having three or more ethylenically unsaturated groups; inorganic fine particles (C); and a photopolymerization initiator (D). The mass ratio (A / B) of the compound (A) to the compound (B) is 30 / 70-80 / 20, and the content ratio of the solvent is 1 mass% or less in 100 mass% of the composition for forming hard coat layers.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition for forming a hard coat layer and a hard coat film.

Background Art

[0002] The composition for forming a hard coat layer (hereinafter referred to as hard coat agent) emphasizes scratch resistance, antifouling property, abrasion resistance, flexibility, transparency for protecting the surface of various substrates, as well as anti-blocking property that prevents sticking when the film coated with the hard coat agent is wound into a roll, and various hard coat agents have been proposed according to applications. On the other hand, in recent years, from the perspectives of environmental conservation and safety at home and abroad, there is a growing trend to reduce or eliminate volatile organic compounds (hereinafter abbreviated as VOC), and environment-friendly hard coat agents that minimize volatile components such as organic solvents have been increasingly adopted. Environment-friendly hard coat agents with minimized VOC such as organic solvents have almost no odor, health hazards, or risk of ignition compared to conventional hard coat agents containing solvents, and no thermal drying oven for volatilizing organic solvents or the like is required, which solves issues related to environment, safety, energy and the like. However, the environment-friendly hard coat agents with minimized VOC have a tendency to increase in viscosity because low-viscosity organic solvents, plasticizers and the like are extremely reduced, making it difficult to apply the hard coat layer thinly and uniformly. In addition, from the viewpoint of coating, if the content of low-viscosity VOC is increased, VOC may remain depending on the drying conditions, and the scratch resistance of the cured film cannot be improved.

[0003] Patent Document 1 proposes a hard coat curing film containing a polyfunctional urethane acrylate, a bifunctional or more functional acrylate, and a monofunctional acrylate compound, which is solvent-free, has a viscosity of 400 to 1200 mPa·s, excellent coating properties, forms a coating film with high hardness, scratch resistance, and excellent adhesion to the substrate, has low warping resistance, and excellent chemical resistance. However, the hard coat curing composition described in Patent Document 1 has difficulties in controlling the film thickness at thinner films and forming a smooth coating film, and the curing film also has problems with antiblocking properties, which are necessary for stable processing when winding the film coated with the hard coat agent and in subsequent secondary processing. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] International Publication No. 2009 / 050957 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] The present invention aims to provide a hard coat layer forming composition that has excellent coating properties and can form a hard coat layer possessing transparency, antiblocking properties, stain resistance, scratch resistance, and curability. [Means for solving the problem]

[0006] The inventors of this invention have conducted extensive research to solve the above problems, and as a result, have arrived at this invention.

[0007] The present invention relates to a hard coat layer forming composition comprising a compound (A) having one or two ethylenically unsaturated groups, a viscosity of 1 to 30 mPa·s at 25°C, and a boiling point of 200°C or higher at 1 atm, a compound (B) having three or more ethylenically unsaturated groups, inorganic fine particles (C), and a photopolymerization initiator (D), wherein the mass ratio (A / B) of compound (A) to compound (B) is 30 / 70 to 80 / 20, and the solvent content is 1.0% by mass or less in 100% by mass of the hard coat layer forming composition.

[0008] The present invention also relates to a hard coat layer forming composition in which, in 100% by mass of compound (A), the content of compound (a1), which has two ethylenically unsaturated groups, a viscosity of 1 mPa·s or more and less than 6 mPa·s at 25°C, and a boiling point of 240°C or higher at 1 atm, is 70% by mass or more.

[0009] Furthermore, the present invention relates to the hard coat layer forming composition, which contains 1.0 part by mass or more and less than 10 parts by mass of inorganic fine particles (C) with respect to a total of 100 parts by mass of compound (A) and compound (B).

[0010] Furthermore, the present invention relates to a hard coat layer forming composition characterized in that the average dispersed particle size (D50) of inorganic fine particles (C) in the hard coat layer forming composition is 20 to 400 nm.

[0011] Furthermore, the present invention relates to the hard coat layer forming composition characterized in that the inorganic fine particles (C) are silica.

[0012] Furthermore, the present invention relates to the hard coat layer forming composition having a viscosity of 20 to 120 mPa·s or less at 25°C.

[0013] Furthermore, the present invention relates to a hard coat film having a light-transmitting substrate and a hard coat layer, wherein the hard coat layer is a cured product of the hard coat layer forming composition. [Effects of the Invention]

[0014] The present invention provides a composition for forming a hard coat layer that is transparent, antiblocking, stain-resistant, and scratch-resistant, and by using this composition. [Modes for carrying out the invention]

[0015] Preferred embodiments of the present invention are described below. In this specification, when "(meth)acrylate" and "(meth)acryloyl" are used, they refer to "acrylate or methacrylate" and "acryloyl or methacryloyl," respectively, unless otherwise specified. Furthermore, compounds (A) having one or two ethylenically unsaturated groups, a viscosity of 1 to 30 mPa·s at 25°C, and a boiling point of 200°C or higher at 1 atm may be abbreviated as "compound (A)," and compounds (B) having three or more ethylenically unsaturated groups may be abbreviated as "compound (B)."

[0016] In this specification, unless otherwise specified, numerical ranges identified using "~" include the numbers before and after "~" as the lower and upper limits.

[0017] ≪Composition for forming a hard coat layer≫ The present invention provides a hard coat layer forming composition comprising: compound (A) having one or two ethylenically unsaturated groups, a viscosity of 1 to 30 mPa·s at 25°C, and a boiling point of 200°C or higher at 1 atm; compound (B) having three or more ethylenically unsaturated groups; inorganic fine particles (C); and a photopolymerization initiator (D), wherein the mass ratio (A / B) of compound (A) to compound (B) is 30 / 70 to 80 / 20, and the solvent content is 1.0% by mass or less per 100% by mass of the hard coat layer forming composition.

[0018] The viscosity of the hard coat layer forming composition at 25°C is preferably 20 to 120 mPa·s. Having a viscosity in this range at 25°C makes it easier to form an even coating film during application, and also makes it easier to control the film thickness to a predetermined value. In the present invention, the viscosity adopted is a value measured with a cone-and-plate E-type viscometer. Details of the measurement method are described in the Examples.

[0019] [Compound (A)] Compound (A) is a compound that has a viscosity of 1 to 30 mPa·s at 25°C, a boiling point of 200°C or higher at 1 atm, and one or two ethylenically unsaturated groups. By using Compound (A), the viscosity of the curable composition can be reduced while minimizing the use of volatile components (organic solvents). In the present invention, the viscosity adopted is a value measured with a cone-and-plate E-type viscometer. Details of the measurement method are described in the Examples. A lower viscosity leads to better coating properties such as coating film smoothness and wettability to the substrate, but if materials are selected only from the perspective of low viscosity, the molecular weight will be too low or the volatility will be too high. Therefore, from the perspectives of coating suitability such as viscosity, safety, and coating film performance, Compound (A) needs to be specified to have a boiling point of 200°C or higher at 1 atm.

[0020] In the film forming method of the present invention, a standby step described later occurs from coating to curing with ultraviolet rays or the like, so that the curable composition liquid disposed on the substrate forms a substantially continuous and stable liquid film. From the perspectives of odor, safety, and coating film performance in the standby step, the boiling point of Compound (A) under normal pressure is preferably 240°C or higher. Lower volatility of Compound (A) tends to be advantageous for the above film formation.

[0021] The number of ethylenically unsaturated groups contained in Compound (A) is preferably 2 from the perspective of the functions of the hard coat layer such as scratch resistance. From the perspective of achieving both coating properties such as viscosity and the functions of the hard coat layer, a mixture of a compound having two ethylenically unsaturated groups and a compound having one ethylenically unsaturated group may also be used.

[0022] Compound (A), which has one or two ethylenically unsaturated groups, a viscosity of 1 to 30 mPa·s at 25°C, and a boiling point of 200°C or higher at 1 atm, is Compound (a1) which has two ethylenically unsaturated groups, has a viscosity at 25°C of 1 mPa·s or more and less than 6 mPa·s, and has a boiling point at 1 atm of 240°C or higher Compound (a2) which has one ethylenically unsaturated group, has a viscosity at 25°C of 1 mPa·s or more and less than 6 mPa·s, and has a boiling point at 1 atm of 240°C or higher, Compound (a3) which has two ethylenically unsaturated groups, has a viscosity at 25°C of 1 mPa·s or more and less than 6 mPa·s, and has a boiling point at 1 atm of 200°C or higher and lower than 240°C, Compound (a4) which has one ethylenically unsaturated group, has a viscosity at 25°C of 1 mPa·s or more and less than 6 mPa·s, and has a boiling point at 1 atm of 200°C or higher and lower than 240°C, Compound (a5) which has two ethylenically unsaturated groups, has a viscosity at 25°C of 6 to 30 mPa·s, and has a boiling point at 1 atm of 200°C or higher and lower than 240°C, Compound (a6) which has one ethylenically unsaturated group, has a viscosity at 25°C of 6 to 30 mPa·s, and has a boiling point at 1 atm of 200°C or higher and lower than 240°C, Compound (a7) which has two ethylenically unsaturated groups, has a viscosity at 25°C of 6 to 30 mPa·s, and has a boiling point at 1 atm of 240°C or higher, It can be classified into compound (a8) which has one ethylenically unsaturated group, has a viscosity at 25°C of 6 to 30 mPa·s, and has a boiling point at 1 atm of 240°C or higher.

[0023] The boiling point at 1 atm can be determined from the reduced-pressure boiling point in catalogs and the like using the boiling point conversion chart described in Science of Petroleum, Vol. II, p. 1281 (1938).

[0024] Examples of the compound (a1) which has two ethylenically unsaturated groups, has a viscosity at 25°C of 1 mPa·s or more and less than 6 mPa·s, and has a boiling point at 1 atm of 240°C or higher, include 2-(2-vinyloxyethoxy)ethyl acrylate (a1-1) (boiling point: 246°C / 760 mmHg, viscosity: 3.65 mPa·s / 25°C), 2-(2-vinyloxyethoxy)ethyl methacrylate (a1-2) (boiling point: 257℃ / 760mmHg, viscosity: 3.19mPa·s / 25℃), 1,4-Butanediol diacrylate (a1-3) (boiling point: 284℃ / 760mmHg, viscosity: 5mPa·s / 25℃) Neopentyl glycol dimethacrylate (boiling point: 275℃ / 760mmHg, viscosity: 5mPa·s / 25℃) 1,4-Butanediol diacrylate (Boiling point: 284℃ / 760mmHg, Viscosity: 5mPa·s / 25℃) Diethylene glycol dimethacrylate (boiling point: 310°C / 760 mmHg, viscosity: 5 mPa·s / 25°C), and, Examples include 1,6-hexanediol diacrylate (boiling point: 329°C / 760 mmHg, viscosity: 5.5 mPa·s / 25°C).

[0025] Compound (a2) having one ethylenically unsaturated group, a viscosity of 1 mPa·s to 6 mPa·s at 25°C, and a boiling point of 240°C or higher at 1 atm, is: Isooctyl acrylate (boiling point: 243℃ / 760mmHg, viscosity: 5mPa·s / 25℃), Benzyl acrylate (boiling point: 249℃ / 760mmHg, viscosity: 2.68mPa·s / 25℃), Ethyl carbitol acrylate (ethoxyethoxyethyl acrylate) (boiling point: 250℃ / 760mmHg, viscosity: 2.9mPa·s / 25℃) Isodecyl acrylate (boiling point: 255℃ / 760mmHg, viscosity: 5mPa·s / 25℃), Isodecyl methacrylate (boiling point: 277℃ / 760mmHg, viscosity: 5mPa·s / 25℃), n-Octyl acrylate (boiling point: 279℃ / 760mmHg, viscosity: 2mPa·s / 25℃), n-dodecyl methacrylate (lauryl methacrylate) (a2-1) (boiling point: 309℃ / 760mmHg, viscosity: 4mPa·s / 25℃), and, Examples include n-dodecyl acrylate (lauryl acrylate) (boiling point: 313℃ / 760mmHg, viscosity: 5mPa·s / 25℃).

[0026] Compound (a3) ​​having two ethylenically unsaturated groups, a viscosity of 1 mPa·s or more and less than 6 mPa·s at 25°C, and a boiling point of 200°C or more and less than 240°C at 1 atm, is: Examples include ethylene glycol dimethacrylate (a3-1) (boiling point: 235℃ / 760mmHg, viscosity: 3mPa·s / 25℃).

[0027] Compound (a4) having one ethylenically unsaturated group, a viscosity of 1 mPa·s or more and less than 6 mPa·s at 25°C, and a boiling point of 200°C or more and less than 240°C at 1 atm, is: Examples include isononyl acrylate (a4-1) (boiling point: 227℃ / 760mmHg, viscosity: 2mPa·s / 25℃) and n-nonyl acrylate (boiling point: 239℃ / 760mHg, viscosity: 2mPa·s / 25℃).

[0028] Compound (a5) having two ethylenically unsaturated groups, a viscosity of 6 to 30 mPa·s at 25°C, and a boiling point of 200°C or higher and less than 240°C at 1 atm, is: Examples include ethylene glycol diacrylate (a5-1) (boiling point: 231.8℃ / 760mmHg, viscosity: 14mPa·s / 25℃).

[0029] Compound (a6) having one ethylenically unsaturated group, a viscosity of 6 to 30 mPa·s at 25°C, and a boiling point of 200°C or higher but less than 240°C at 1 atm, is 2-ethylhexyl diglycol acrylate (a6-1) (boiling point: 213°C / 760 mmHg, viscosity: 7 mPa·s / 25°C).

[0030] Compound (a7) having two ethylenically unsaturated groups, a viscosity of 6-30 mPa·s at 25°C, and a boiling point of 240°C or higher at 1 atm, is: Dicyclopentenyl acrylate (boiling point: 258℃ / 760mmHg, viscosity: 9mPa·s / 25℃), Neopentyl glycol diacrylate (boiling point: 281℃ / 760mmHg, viscosity: 6.5mPa·s / 25℃), 1,4-Butanediol dimethacrylate (boiling point: 284℃ / 760mHg, viscosity: 7mPa·s / 25℃), 3-Methyl-1,5-pentanediol diacrylate (boiling point: 289℃ / 760mmHg, viscosity: 8mPa·s / 25℃), 1,3-Butylene glycol dimethacrylate (boiling point: 290℃ / 760mHg, viscosity: 7mPa·s / 25℃), 1,3-Butylene glycol diacrylate (boiling point: 290℃ / 760mmHg, viscosity: 8mPa·s / 25℃), Dicyclopentenyloxyethyl acrylate (boiling point: 298℃ / 760mmHg, viscosity: 20mPa·s / 25℃), Dipropylene glycol diacrylate (boiling point: 313℃ / 760mmHg, viscosity: 8mPa·s / 25℃), Dicyclopentenyloxyethyl methacrylate (boiling point: 314℃ / 760mmHg, viscosity: 17.5mPa·s / 25℃), 1,6-Hexanediol dimethacrylate (boiling point: 315℃ / 760mHg, viscosity: 6mPa·s / 25℃), 1,6-Hexanediol acrylic acid polymer ester (boiling point: 329°C / 760 mmHg, viscosity: 6 mPa·s / 25°C), Triethylene glycol dimethacrylate (boiling point: 337°C / 760mHg, viscosity: 9mPa·s / 25°C), 1,9-nonanediol diacrylate (boiling point: 342℃ / 760mmHg, viscosity: 8mPa·s / 25℃), Triethylene glycol diacrylate (boiling point: 354℃ / 760mmHg, viscosity: 9.5mPa·s / 25℃), Tripropylene glycol diacrylate (a7-1) (boiling point: 362℃ / 760mmHg, viscosity: 14mPa·s / 25℃), Tetraethylene glycol diacrylate (boiling point: 363°C / 760 mmHg, viscosity: 11 mPa·s / 25°C), and, Examples include 1,9-nonanediol dimethacrylate (boiling point: 372°C / 760mHg, viscosity: 8mPa·s / 25°C).

[0031] Compound (a8) having one ethylenically unsaturated group, a viscosity of 6 to 30 mPa·s at 25°C, and a boiling point of 240°C or higher at 1 atm, is: 2-(2-ethoxyethoxy)ethyl acrylate (boiling point: 250℃ / 760mmHg, viscosity: 6mPa·s / 25℃), Isobornyl acrylate (boiling point: 254℃ / 760mHg, viscosity: 7.7mPa·s / 25℃) (a8-1) Isobornyl methacrylate (boiling point: 255℃ / 760mHg, viscosity: 6mPa·s / 25℃) Phenoxyethyl methacrylate (boiling point: 260°C / 760mHg, viscosity: 7mPa·s / 25°C) Dicyclopentanyl acrylate (boiling point: 278℃ / 760mHg, viscosity: 12mPa·s / 25℃) Dicyclopentanyl methacrylate (boiling point: 284°C / 760mHg, viscosity: 12mPa·s / 25°C) n-Tridecyl acrylate (boiling point: 291℃ / 760mHg, viscosity: 7mPa·s / 25℃), Phenoxyethyl acrylate (boiling point: 293°C / 760mHg, viscosity: 9mPa·s / 25°C) Phenoxydiethylene glycol acrylate (boiling point: 293°C / 760mHg, viscosity: 16mPa·s / 25°C) Isostearyl acrylate (boiling point: 313℃ / 760mHg, viscosity: 17mPa·s / 25℃) n-Stearyl methacrylate (boiling point: 380°C / 760mHg, viscosity: 11mPa·s / 25°C), and, Examples include n-stearyl acrylate (boiling point: 403°C / 760mHg, viscosity: 8.5mPa·s / 25°C).

[0032] Compounds (a1) and (a2) are preferred in terms of physical properties such as low viscosity, odor, safety, and curability, and compound (a1) is more preferred in terms of scratch prevention. Among the compounds (a1), 2-(2-vinyloxyethoxy)ethyl acrylate and 2-(2-vinyloxyethoxy)ethyl methacrylate, which have a viscosity of 4 mPa·s or less at 25°C, are preferred, with 2-(2-vinyloxyethoxy)ethyl acrylate being particularly preferred. These compounds have a high effect as a low-viscosity reactive diluent, and because they possess two types of ethylenically unsaturated groups, a radical polymerization-promoting acryloyl group and a cationic polymerization-promoting vinyl ether group, they are less susceptible to oxygen inhibition and have high reactivity, which makes it easier to improve physical properties such as curability and scratch resistance.

[0033] From the viewpoint of achieving both low viscosity, low odor, safety, and scratch resistance, the content of compound (a1) in 100% by mass of compound (A) is preferably 70% by mass or more, and from the viewpoint of improving coating properties, 75% by mass or more is more preferable. A higher content improves the strength of the coating film, and a coating film that can withstand scratch resistance can be formed. From the viewpoint of curing shrinkage, the content of compound (a1) is preferably less than 100% by mass.

[0034] [Compound (B)] Compound (B) is a compound having three or more ethylenically unsaturated groups. Examples of compound (B) include pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, PO-modified trimethylolpropane tri(meth)acrylate, tris(acryloxyethyl) isocyanurate, caprolactone-modified tris(acryloxyethyl) isocyanurate, trimethylolethane tri(meth)acrylate, and dipentaerythritol tetra(meth)acrylate. Ester compounds of polyhydric alcohols and (meth)acrylic acid, such as acrylates, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, alkyl-modified dipentaerythritol tri(meth)acrylate, alkyl-modified dipentaerythritol tetra(meth)acrylate, alkyl-modified dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, and 1,2,3-cyclohexanetetra(meth)acrylate; Poly(meth)acrylate compounds of polyfunctional compounds such as polyurethane poly(meth)acrylate, polyester poly(meth)acrylate, polyether poly(meth)acrylate, polyacrylic poly(meth)acrylate, polyalkyd poly(meth)acrylate, polyepoxy poly(meth)acrylate, polyspiroacetal poly(meth)acrylate, polybutadiene poly(meth)acrylate, polythiol polyene poly(meth)acrylate, and polysilicon poly(meth)acrylate; Examples include ester compounds synthesized from polyhydric alcohols, polybasic acids, and (meth)acrylic acid, such as ester compounds synthesized from trimethylolethane / succinic acid / acrylic acid = 2 / 1 / 4 (molar ratio).

[0035] From the viewpoint of adhesion and scratch resistance, compound (B) is preferably dipentaerythritol pentaacrylate, dipentaerythritol hexa(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, polyurethane poly(meth)acrylate, polyester poly(meth)acrylate, polyether poly(meth)acrylate, and polyacrylic poly(meth)acrylate. (b)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, polyurethane poly(meth)acrylate, and polyester poly(meth)acrylate are preferred, and from the viewpoint of viscosity adjustment, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate (b1), pentaerythritol triacrylate, pentaerythritol tetraacrylate (b2), and trimethylolpropane triacrylate (b3) are more preferred.

[0036] The mass ratio (A / B) of compound (A) to compound (B) is 30 / 70 to 80 / 20. Within this range, the coating strength is further improved without increasing viscosity, and a coating that can withstand adhesion to the substrate and scratch resistance can be formed. From the viewpoint of further improving coating properties, 35 / 65 to 65 / 35 is more preferable.

[0037] [Inorganic fine particles (C)] Inorganic particles (C) primarily play a role in providing antiblocking properties. The shape of the inorganic particles (C) is not limited, but for example, spherical or crushed particles can be used.

[0038] Examples of inorganic fine particles (C) include silica, alumina, aluminum hydroxide, chromium oxide, iron oxide, zirconium oxide, zinc oxide, titanium oxide, barium sulfate, magnesium oxide, glass beads, titanium, carbon black, graphene, graphite, and diamond. From the viewpoint of antiblocking properties, silica is preferred as the inorganic fine particles (C).

[0039] The surface of the inorganic fine particles (C) may be subjected to a surface treatment containing an organic compound. Reactive inorganic fine particles may also be used. Reactive inorganic fine particles are obtained by surface-modifying inorganic fine particles with a compound having a reactive group. Reactive inorganic fine particles are inorganic fine particles that react upon heating or irradiation with active energy rays, and examples include particles having reactive groups such as polymerizable vinyl groups, ethylenically unsaturated groups such as (meth)acryloyl groups, and epoxy groups on their surface. As surface treatment agents, for example, known treatment agents such as silane coupling agents like 3-(meth)acryloxypropyltrimethoxysilane, β-ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, hexamethyldisilazane, and dimethyldichlorosilane, or silicone oil can be used.

[0040] The average dispersed particle size (D50) of inorganic fine particles (C) in the hard coat layer forming composition is preferably 20 to 400 nm, and more preferably 100 to 300 nm. This range is preferable because it allows for the formation of a coating film that combines transparency (low haze) and antiblocking properties. Furthermore, the preferred primary particle size for obtaining the above-mentioned dispersed particle size is 10 to 200 nm, more preferably 20 to 150 nm.

[0041] In the present invention, the average dispersed particle diameter (D50) in the hard coat layer forming composition for inorganic fine particles (C) refers to the average particle diameter (median diameter = D50) of inorganic fine particles (C) when the hard coat layer forming composition is measured using Microtrac-Bell's "UPA150-EX". The primary particle diameter is the smallest unit of particles, and is the average particle diameter of solid particles that have a boundary between particles that is recognized as being unable to be divided any further. This is usually determined by transmission electron microscope images or the like. Details of the method for measuring the dispersion particle size of inorganic fine particles (C) in a hard coat layer formation composition are described in the Examples section.

[0042] The content of inorganic fine particles (C) is preferably 1.0 part by mass or more and less than 10 parts by mass per 100 parts by mass of the total of compound (A) and compound (B). More preferably, it is 2.5 to 4.5 parts by mass. By including it in the range of 1.0 part by mass or more and less than 10 parts by mass, a hard coat forming composition with improved transparency and smoothness and excellent antiblocking properties can be obtained.

[0043] When inorganic fine particles (C) are pre-dispersed with compound (A), the viscosity of the hard coat forming composition tends to stabilize. This improves the coatability, transparency, and smoothness, resulting in a hard coat forming composition with excellent antiblocking properties.

[0044] [Photopolymerization initiator (D)] The photopolymerization initiator (D) is not particularly limited as long as it has the function of initiating radical polymerization by photoexcitation, and examples include acetophenone compounds, benzoin compounds, benzophenone compounds, phosphine oxide compounds, ketal compounds, anthraquinone compounds, and thioxanthone compounds. Specifically, examples include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, diethoxyacetophenone, benzyldimethyl ketal, 1-hydroxycyclohexylphenyl ketone, benzophenone, 2,4,6-trimethylbenzoin diphenylphosphine oxide, N,N-dimethylaminobenzoate isoamyl, 2-chlorothioxanthone, and 2,4-diethylthioxanthone. In addition, known organic amines can be added as sensitizers.

[0045] The content of the photopolymerization initiator (D) is preferably 0.1 to 20 parts by mass, and more preferably 1 to 15 parts by mass, per 100 parts by mass of the total of compound (A) and compound (B). Within this range, a sufficient polymerization initiation effect is obtained, which is effective in improving adhesion and scratch resistance.

[0046] The hard coat layer forming composition in the present invention may further contain a sensitizer. By using a photopolymerization initiator and a sensitizer in combination, the photoreactivity can be enhanced. Examples of sensitizers include amine-based sensitizers, anthracene-based sensitizers, and thioxanthone-based sensitizers. Examples of amine-based sensitizers include trimethylamine, methyldimethanolamine, triethanolamine, p-diethylaminoacetophenone, ethyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, N,N-dimethylbenzylamine, and 4'-bis(diethylamino)benzophenone. Examples of anthracene-based sensitizers include 9,10-dibutoxyanthracene, 9,10-diethoxyanthracene, 9,10-dipropoxyanthracene, and 9,10-bis(2-ethylhexyloxy)anthracene. Thioxanthone-based sensitizers include, for example, 2,4-diethylthioxanthone, 2-isopropylthioxanthone, and 4-isopropylthioxanthone. Representative examples of commercially available products include EPA (manufactured by Nippon Kayaku Co., Ltd.) for amine-based sensitizers, DBA and DEA (manufactured by Kawasaki Chemical Industries, Ltd.) for anthracene-based sensitizers, and DETX and ITX (manufactured by Lambson) for thioxanthone-based sensitizers. Thioxanthone-based sensitizers are preferred because, in addition to their reactivity, they produce less discoloration after the reaction compared to other amine-based sensitizers. When a sensitizer is used, its content is preferably 0.1 to 10 parts by mass per 100 parts by mass of the total of compound (A) and compound (B).

[0047] The hard coat layer forming composition of the present invention may optionally contain other additives. Examples of other additives include plasticizers, surface modifiers, light stabilizers, antioxidants, and polymerization inhibitors.

[0048] In the hard coat layer forming composition of the present invention, the solvent content is preferably 1.0% by mass or less, and preferably substantially solvent-free. However, a small amount of solvent may be included for the purpose of increasing the solubility of photopolymerization initiators, sensitizers, and other additives.

[0049] As for solvents, while odor is a factor, known solvents include aromatic organic solvents such as toluene and xylene, ketone organic solvents such as methyl ethyl ketone and methyl isobutyl ketone, ester organic solvents such as ethyl acetate, n-propyl acetate, isopropyl acetate, and isobutyl acetate, alcohol organic solvents such as methanol, ethanol, n-propanol, isopropanol, and n-butanol, and glycol ether organic solvents such as propylene glycol monomethyl ether.

[0050] The solvent content in the hard coat layer forming composition is preferably 1.0 part by mass or less, and more preferably 0.5 part by mass or less. Within this range, a sufficient polymerization initiation effect is obtained, which is effective in improving adhesion and scratch resistance.

[0051] <Method for producing a composition for forming a hard coat layer> The hard coat layer forming composition of the present invention contains compound (A), compound (B), inorganic fine particles (C), a photopolymerization initiator (D), and optionally a sensitizer and other additives. The manufacturing method is not particularly limited, but in order to reduce the use of solvents, it is preferable to pre-disperse the inorganic fine particles (C) using low viscosity compound (A), add and dissolve the photopolymerization initiator (D) therein, and then add compound (B) and disperse and stir to produce a hard coat layer forming composition with good dispersibility. Furthermore, there is no problem using known dispersants or surface treatment agents during dispersion, and commercially available products are available. SIRTPGDA30WT%-P02, SIRTPGDA50WT%-P08, Dispersed silica such as SIRTPGDA60WT%-P05 (CIK Nanotech), Nanocryl C150 (ARKEMA), and Optisol ASAM2100 (RANCO). Sol-type products can be used.

[0052] ≪Hard Coat Film≫ The hard coat film of the present invention comprises a light-transmitting substrate and a hard coat layer. The hard coat layer is a cured product of the hard coat layer forming composition of the present invention.

[0053] While not specifically mentioned, common light-transmitting film substrates such as polyethylene terephthalate (PET), triacetylcellulose (TAC), polycarbonate, cycloolefin polymer (COP), and acrylic can be used as light-transmitting substrates.

[0054] While there are generally no specific regulations regarding the thickness of the hard coat layer, as long as it can be cured by irradiation with ultraviolet light after coating, it is often implemented within the range of 2 μm to 15 μm for practical reasons.

[0055] The method for manufacturing a hard coat film is not particularly limited and can be conventionally known, such as coating a hard coat layer-forming composition onto a light-transmitting substrate. For example, the hard coat layer forming composition of the present invention is applied to a polyethylene terephthalate substrate, and the solvent is dried as needed. By irradiating the surface with active energy rays, the applied hard coat layer forming composition is crosslinked and cured, resulting in a hard coat film having a polyethylene terephthalate substrate and a hard coat layer.

[0056] Coating methods include bar coating, blade coating, spin coating, reverse coating, dyeing, spray coating, roll coating, gravure coating, microgravure coating, lip coating, air knife coating, and dipping.

[0057] As active energy rays, electron beams and ultraviolet rays emitted from light sources such as xenon lamps, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, carbon arc lamps, and tungsten lamps can be used. [Examples]

[0058] The present invention will be described in more detail below. The present invention is not limited to the examples. Note that "parts by mass" will be written as "parts" and "% by mass" will be written as "%".

[0059] The abbreviations for the materials used in the examples are explained below.

[0060] (a1-1): VEEA: 2-(2-vinyloxyethoxy)ethyl acrylate, boiling point: 246℃ / 760mmHg, viscosity: 3.65mPa·s / 25℃, manufactured by Nippon Shokubai Co., Ltd. (a1-2): VEEM: 2-(2-vinyloxyethoxy)ethyl methacrylate, boiling point: 257℃ / 760mmHg, viscosity: 3.19mPa·s / 25℃, manufactured by Nippon Shokubai Co., Ltd. (a1-3): 14BDDA: 1,4-butanediol diacrylate, boiling point: 284℃ / 760mmHg, viscosity: 5mPa·s / 25℃, manufactured by Osaka Organic Chemical Industry Co., Ltd., Viscoat #195 (a2-1): LMA: Dodecyl methacrylate (lauryl methacrylate), boiling point: 309℃ / 760mmHg, viscosity: 4mPa·s / 25℃, manufactured by Mitsubishi Chemical Corporation. (a2-2): BZA: Benzyl acrylate, boiling point: 249℃ / 760mmHg, viscosity: 2.68 mPa·s / 25℃, manufactured by Osaka Organic Chemical Industry Co., Ltd., Viscoat #160 (a3-1): EG-DMA: Ethylene glycol dimethacrylate, boiling point 235℃ / 760mmHg, viscosity 3mPa·s / 25℃, NK Ester 1G manufactured by Shin Nakamura Chemical Co., Ltd. (a4-1): INAA: Isononyl acrylate, boiling point: 227℃ / 760mmHg, viscosity: 2mPa·s / 25℃, manufactured by Osaka Organic Chemical Industry Co., Ltd. (a5-1):EG-DA: Ethylene glycol diacrylate, boiling point: 231.8℃ / 760mmHg, viscosity: 14mPa·s / 25℃, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. (a6-1): EHDG-A: 2-Ethylhexyl diglycol acrylate, boiling point: 214℃ / 760mmHg, viscosity: 7mPa·s / 25℃, light acrylate EHDG-AT: Manufactured by Kyoeisha Chemical Co., Ltd. (a7-1): TPG-DA: Tripropylene glycol diacrylate, boiling point: 362℃ / 760mmHg, viscosity: 14mPa·s / 25℃, Viscoat #310HP: Manufactured by Osaka Organic Chemical Industry Co., Ltd. (a8-1): IBXA: Isobornyl acrylate, boiling point: 254℃ / 760mHg, viscosity: 7.7mPa·s / 25℃, IBXA: Manufactured by Osaka Organic Chemical Industry Co., Ltd.

[0061] (f1): MMA: Methyl methacrylate, boiling point 144℃ / 760mmHg, 0.72mPa·s / 25℃, manufactured by Mitsubishi Gas Chemical Company. (f2): DCP-DA: Dimethylol-tricyclodecane diacrylate, boiling point: 342℃ / 760mmHg, viscosity: 150mPa·s / 25℃, light acrylate DCP-A: Manufactured by Kyoeisha Chemical Co., Ltd.

[0062] (B1): DPHA-2C: A mixture of dipentaerythritol hexaacrylate (b1) and pentaerythritol tetraacrylate (b2) = 60 / 40. KARAYAD DPHA-2C: Manufactured by Nippon Kayaku Co., Ltd. (B2): DPHA: Dipentaerythritol hexaacrylate (b1), MIRAMER M-600: Manufactured by MIWON Corporation • (B3): PE-4A: Pentaerythritol tetraacrylate (b2), MIRAMER M420: Manufactured by MIWON Corporation • (B4): TMP-3A: Trimethylolpropane triacrylate (b3), SARTOMER SR-351S: Manufactured by ARKEMA

[0063] • (c1): SIRTPGDA30WT%-P02, primary particle size 30 nm, silica dispersion (silica: 30% by mass, tripropylene glycol diacrylate (a2-1): 70% by mass, manufactured by CIK Nanotech) • (c2): SIRTPGDA50WT%-P08, primary particle size 100nm, silica dispersion (silica: 50% by mass, tripropylene glycol diacrylate (a2-1): 50% by mass), manufactured by CIK Nanotech. • (c3): SIRTPGDA60WT%-P05, primary particle size 300nm, silica dispersion (silica: 60% by mass, tripropylene glycol diacrylate (a2-1): 40% by mass), manufactured by CIK Nanotech. • (c4): Optisol ASAM2100, primary particle size 12 nm, silica dispersion (silica: 50% by mass, tripropylene glycol diacrylate (a2-1): 50% by mass), manufactured by RANCO.

[0064] • (d1): OMNIRAD 1173, 2-hydroxy-2-methyl-1-phenylpropanone, manufactured by IGM RESINS. (d2): OMNIRAD 184, 1-hydroxycyclohexyl phenyl ketone, manufactured by IGM RESINS. • (d3): ESACURE ONE, 1-propanone, 2-hydroxy-2-methyl-1-[4-(1-methylethenyl)phenyl]-, homopolymer, manufactured by IGM RESINS. • (d4): IRGACURE OEX01, 1,2-octanedione, 1-[4-(phenylthio)phenyl]-,2-(o-benzoyloxime), manufactured by BASF Japan.

[0065] (e1): PGM: Propylene glycol monomethyl ether, boiling point: 120℃ / 760mHg, viscosity: 1.9mPa·s / 20℃, manufactured by Sankyo Chemical Co., Ltd.

[0066] <Example 1> In a light-shielded glass bottle, 26 parts of a1-1 (VEEA), 50 parts of DPHA-2C (30 parts of (b1), 20 parts of (b2)), 3.6 parts of c1 (SIRTPGDA30WT%-P02), 8 parts of d1 (OMNIRAD 1173), and 4 parts of OMNIRAD 184 were placed and mixed with a mixing rotor to obtain composition 1 for forming a hard coat layer.

[0067] Next, hard coat layer forming composition 1 was applied to a 50 μm thick PET film (Lumirror U403 manufactured by Toray Industries, Inc.) so that the film thickness after curing would be 5 μm. After irradiating with ultraviolet light from a high-pressure mercury lamp with an output of 80 w / cm, the coated layer was cured to obtain a hard coat film 1.

[0068] <Examples 2-42, Comparative Examples 1-8> As shown in Tables 1-4, hard coat layer forming compositions for Examples 2-42 and Comparative Examples 1-8 were prepared in the same manner as in Example 1, except for changes in composition, and hard coat films were obtained using each of them.

[0069] [measurement] The dispersion particle size and viscosity of the hard coat layer forming compositions obtained in each example and comparative example were measured using the following method. The results are shown in Tables 1 to 4.

[0070] [Measurement of mean dispersion particle size (D50)] The average dispersed particle size (D50) in the hard coat layer forming composition was measured using a dynamic light scattering particle size distribution analyzer (Microtrac-Bel "UPA150-EX"). In this invention, methyl ethyl ketone was used as the solvent, and the average value of three 60-second measurements was taken at a concentration where the loading index was in the range of 1.0 ± 0.2.

[0071] [Viscosity measurement] The viscosity of the obtained hard coat layer forming composition was measured under the following conditions. E-type viscometer: VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) Rotation speed 20 rpm, rotor No. 1, 25℃, 1 minute value The measurement results were classified according to the following criteria. The results are shown in Tables 1-4. A: 20 mPa·s or more and less than 60 mPa·s B: 60mPa·s or more, 120mPa·s or less C: Less than 20 mPa·s or greater than 120 mPa·s

[0072] [Table 1]

[0073] [Table 2]

[0074] [Table 3]

[0075] [Table 4]

[0076] [evaluation] The hard coat films prepared using the hard coat layer-forming compositions obtained in each example and comparative example were evaluated using the following method. The results are shown in Tables 5 to 8.

[0077] [Coating properties] The appearance of the obtained hard coat film was visually observed and evaluated under the following conditions. 3: The painted surface was even: Good 2: There were some inconsistencies in the coating: Usable 1: Unevenness across the entire painted surface: Unusable

[0078] [Transparency] The obtained hard coat film was cut into 10cm x 10cm pieces, and the haze value was measured using a spectroscopic haze meter (SH7000, manufactured by Nippon Denshoku Industries Co., Ltd.). Transparency was evaluated according to the following evaluation criteria. • Evaluation criteria 4: Haze value less than 0.3%: Excellent 3: Haze value between 0.3% and 0.5%: Good 2: Haze value between 0.5% and 1.0%: Usable 1: Haze value of 1.1% or higher: Not practical.

[0079] [Antiblocking properties] The antiblocking properties were evaluated by observing whether or not the two hard coat films, with their coated surfaces facing each other, stuck together when slid horizontally. • Evaluation criteria 4: No sticking between coated surfaces, smooth: Excellent 3: There is some sticking between coated surfaces only at the edges, but it is slippery: Good 2: There is some sticking between coated surfaces, not just at the edges, but it is still slippery: usable. 1: The coated surfaces stick together and do not slide: Unusable.

[0080] [Scratch-resistant] A 1-square-centimeter rectangular pad fitted with #0000 steel wool was placed on the sample surface, and after 10 back-and-forth passes with a load of 200g, the appearance was visually evaluated and the number of scratches was measured. • Evaluation criteria 5: No scratches: Excellent condition 4: 1 to 3 scratches: Excellent 3: 3 to 7 scratches: Good 2: 7 to less than 10 scratches: Usable 1: More than 10 scratches: Unusable

[0081] [Adhesion] Nichiban's cellophane tape (registered trademark) was applied to the obtained hard coat film, then peeled off forcefully, and the degree to which it peeled off was evaluated. • Evaluation criteria 3: No peeling: Good 2: Peeling occurs in an area exceeding 0% but less than 10% of the area where the cellophane tape is applied: Usable. 1: Peeling occurs in more than 10% of the area where the cellophane tape is applied: Unusable.

[0082] [Curability] The resulting hard coat film was visually evaluated by rubbing the surface with a cloth gauze to see if any marks were left. • Evaluation criteria 4: Leaves no trace: Excellent 3: Some marks remain: Good 2: Faint marks appear all over: Usable 1: Clear marks are left all over: Unusable

[0083] [Table 5]

[0084] [Table 6]

[0085] [Table 7]

[0086] [Table 8]

Claims

1. The material contains a compound (A) having one or two ethylenically unsaturated groups, a viscosity of 1 to 30 mPa·s at 25°C, and a boiling point of 200°C or higher at 1 atm, a compound (B) having three or more ethylenically unsaturated groups, inorganic fine particles (C), and a photopolymerization initiator (D). The mass ratio (A / B) of compound (A) to compound (B) is 30 / 70 to 80 / 20. A hard coat layer forming composition wherein the solvent content is 1% by mass or less in 100% by mass of the hard coat layer forming composition, In 100% by mass of the aforementioned compound (A), the content of compound (a1), which has two ethylenically unsaturated groups, a viscosity of 1 mPa·s or more and less than 6 mPa·s at 25°C, and a boiling point of 240°C or higher at 1 atm, is 70% by mass or more. The compound (a1) comprises 2-(2-vinyloxyethoxy)ethyl acrylate, 2-(2-vinyloxyethoxy)ethyl methacrylate, or 1,4-butanediol diacrylate. The compound (A) further comprises a compound (a7) having two ethylenically unsaturated groups, a viscosity of 6 to 30 mPa·s at 25°C, and a boiling point of 240°C or higher at 1 atm. The primary particle size of the inorganic fine particles (C) is 10 to 200 nm. A hard coat layer forming composition comprising 1.0 part by mass or more and less than 10 parts by mass of the inorganic fine particles (C) with respect to a total of 100 parts by mass of the compound (A) and the compound (B).

2. The hard coat layer forming composition according to claim 1, wherein the inorganic fine particles (C) are contained in an amount of 2.5 parts by mass or more and less than 4.5 parts by mass per 100 parts by mass of the total of compound (A) and compound (B).

3. The hard coat layer forming composition according to claim 1, characterized in that the average dispersed particle size (D50) of the inorganic fine particles (C) in the hard coat layer forming composition is 20 to 400 nm.

4. The hard coat layer forming composition according to claim 1, characterized in that the inorganic fine particles (C) are silica fine particles.

5. The hard coat layer forming composition according to claim 1, wherein the viscosity at 25°C is 20 to 120 mPa·s.

6. A hard coat film having a light-transmitting substrate and a hard coat layer, wherein the hard coat layer is a cured product of the hard coat layer forming composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Hardening type composition for coating

    JP2004277570A

  • Polycarbonate resin laminate

    JP2011183758A

  • Composition for hard coat

    JP2012107225A

  • Ultraviolet-curable antiblocking hard coat resin composition and antiblocking hard coat film

    JP2017226787A

  • Solvent-free hard coat resin composition and optical laminate including the same

    JP2024115675A